THE INFLUENCE OF PARTICIPATION IN BUDGET PREPARATION ON MANAGERIAL PERFORMANCE AT PT PLN (PERSERO) DISTRIBUTION MAIN UNIT AND SULAWESI LOAD MANAGEMENT CENTER - Johannes Baptista Halik; Yemima Yemima; Maria Yessica Halik (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This research aims to determine the effect of participation in budget preparation on managerial performance at PT. PLN (Persero) Main Distribution Unit and Sulawesi Load Control Center, reviewed based on Descriptive Statistics. The number of samples taken was 60 people using the Slovin formula. As a data collection technique, a questionnaire was used, then the data was processed using the SPSS Version 25 application. After the data was processed and analyzed, it was found that the participation of budget preparers (X) had a positive and significant effect on managerial performance (Y). For this reason, the author suggests that PT. PLN (Persero), Main Distribution Unit and Sulawesi Expense Management Center, maximizes and increases the participation of assistant managers, supervisors, unit managers and related staff in budget preparation so that their managerial performance will also improve, thus having a positive impact on the company's development. Keywords: Participation, Budget Preparation, Managerial Performance, PT. PLN, Makassar